Annihilation [videorecording (DVD)] - Garland, Alex, 1970-; Portman, Natalie, 1981-; Leigh, Jennifer Jason, 1962-; Rodriguez, Gina, 1984-; VanderMeer, Jeff (Paramount, 2018)
Biologist and former soldier Lena is shocked when her missing husband comes home near death from a top-secret mission into The Shimmer, a mysterious quarantine zone from which no one has ever returned. Now, Lena and her elite team must enter a beautiful, deadly world of mutated landscapes and creatures, to discover how to stop the growing phenomenon that threatens all life on Earth.